The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5539/elt.v6n12p38
|View full text |Cite
|
Sign up to set email alerts
|

Relations among L1 Reading, L2 Knowledge, and L2 Reading: Revisiting the Threshold Hypothesis

Abstract: This study attempted to test the threshold hypothesis in second/foreign language (L2) reading by investigating the relations among first language (L1) reading, L2 knowledge, and L2 reading comprehension in a sample of 2666 (1333 males and 1333 females) Korean EFL high school students. Three different methods of data analysis were utilized after closely looking into the methods of data analysis of the current literature on a language threshold. Statistical analysis revealed that the contribution of L1 reading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 17 publications
3
14
0
1
Order By: Relevance
“…Using these measures, Jiang (2011) and Park (2013) found L2 knowledge to be a better predictor of L2 reading than L1 literacy, thus confirming the results of previous research as well as Bernhardt's (2011) model. However, unlike previous studies that found a positive relationship between L2 knowledge and the variance accounted for by L1 literacy, Park (2013) found that the predictive power of L1 literacy decreased as L2 knowledge increased.…”
Section: The Predictive Power Of L1 Literacy and L2 Knowledgesupporting
confidence: 78%
See 3 more Smart Citations
“…Using these measures, Jiang (2011) and Park (2013) found L2 knowledge to be a better predictor of L2 reading than L1 literacy, thus confirming the results of previous research as well as Bernhardt's (2011) model. However, unlike previous studies that found a positive relationship between L2 knowledge and the variance accounted for by L1 literacy, Park (2013) found that the predictive power of L1 literacy decreased as L2 knowledge increased.…”
Section: The Predictive Power Of L1 Literacy and L2 Knowledgesupporting
confidence: 78%
“…Using this reduced form of the threshold hypothesis of bilingual cognitive competence to a theoretical threshold of L2 proficiency needed to successful transfer of L1 skills to L2 reading, many researchers have attempted to answer Alderson's question (e.g. Bernhardt & Kamil, 1995;Brisbois, 1995;Jiang, 2011;Lee & Schallert, 1997, Park, 2013. The intention of the threshold hypothesis, however, was not to send researchers to look for the minimal level of L2 knowledge necessary to understand L2 texts.…”
Section: The Interdependence Hypothesis and Common Underlying Proficimentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, application of schema theory (Zhao & Zhu, 2012), use of different model of reading like class discussion, and small group discussion (Shen, 2013;Hamra & Syatriana, 2012) teaching English through MI theory (Jing, 2013), adoption of cooperative learning (Pan & Wu, 2013), use of graphic organizer (D & Rajan, 2013), adoption of reading techniques of SQ3R i.e. survey, question, read, recite and review (Attaprechakul, 2013& Mohammadi, Heidari, & Niry, 2012, use of metacognitive reading strategy (Ahmadi, Ismail, & Abdullah, 2013), use of fill in the map version of concept map technique (Soleimani & Nabizadeh, 2012), use of novel as a reading text (Tsai, 2012), use of authentic material (Guo, 2012), focus on language based approaches and strategy based approaches (Park, 2013) are found effective techniques to enhance learners' reading comprehension. In the virtual world of ELT, the use of blogs (Kashani, Mahmud, & Kalajahi, 2013) and application of blended learning (Alzumor et al, 2013) can also be beneficial for the enhancement of learners' reading comprehension.…”
Section: Teaching Reading Skillmentioning
confidence: 99%